2008
DOI: 10.1007/s00018-008-8494-3
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous retroviruses

Abstract: Endogenous retrovirus-like elements, or ERVs, are an abundant component of all eukaryotic genomes. Their transcriptional and retrotranspositional activities have great potential for deleterious effects on gene expression. Consequences of such activity may include germline mutagenesis and cancerous transformation. As a result, mammalian genomes have evolved means of counteracting ERV transcription and mobilization. In this review, we discuss epigenetic mechanisms of ERV and LTR retrotransposon control during mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(77 citation statements)
references
References 187 publications
(273 reference statements)
2
71
1
Order By: Relevance
“…4), while the lack of enrichment in other cell populations could exemplify the indirect mechanism regulating HML-2 expression in HIV-1-infected patients. The differences in the magnitude of HML-2 transcription in cell subsets could be due to cell-specific transcription factors, methylation patterns, or other epigenetic changes, which are believed to control endogenous retrovirus expression in differentiated tissues (60,61). Based on these results, it appears that differential expression from multiple cell sources may lead to the 2-fold difference in HML-2 expression in HIV-infected versus control individuals.…”
Section: Discussionmentioning
confidence: 96%
“…4), while the lack of enrichment in other cell populations could exemplify the indirect mechanism regulating HML-2 expression in HIV-1-infected patients. The differences in the magnitude of HML-2 transcription in cell subsets could be due to cell-specific transcription factors, methylation patterns, or other epigenetic changes, which are believed to control endogenous retrovirus expression in differentiated tissues (60,61). Based on these results, it appears that differential expression from multiple cell sources may lead to the 2-fold difference in HML-2 expression in HIV-infected versus control individuals.…”
Section: Discussionmentioning
confidence: 96%
“…As other retrotransposons, IAPs are generally maintained in the silenced state by repressive epigenetic modifications (reviewed in [8]). A major contributor for IAP silencing is DNA (5-cytosine) methylation.…”
Section: Epigenetic Regulation Patterns Of Iaps Differ Among Tissuesmentioning
confidence: 99%
“…A recent study has estimated that there could be at least 32 previously identified germline mutations caused by IAPs in mice, which account for roughly 5 per cent of all such incidents reported so far [8]. These include two well analysed loci, namely, the agouti viable yellow (A VY ) and the Axin-fused (Axin FU ) alleles, which arise from IAP insertions in the promoter and intronic regions of the agouti and the Axin loci, respectively [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of cells with a chemical inhibitor specific for G9a increases the efficiency of iPS cell generation [56]. Although the molecular significance of silencing is unknown, ES cells are considered to be a good model for studying the relationship between DNA methylation and histone modifications, because of their high level of de novo DNA methyltransferase activity [57]. Endogenous retroviruses (ERVs) are transcriptionally silenced in ES cells.…”
Section: Distinct Histone Modification Profile In Pluripotent Cellsmentioning
confidence: 99%